1997
DOI: 10.1097/00004836-199710000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Acid Secretion Over the Years

Abstract: We studied the effect of aging on gastric acid secretion in 11 physicians who had augmented histamine tests while at medical school in 1962. One of them had a duodenal ulcer at the time. The augmented histamine test was repeated in 1991 and, in addition, upper gastrointestinal endoscopy was done to exclude peptic ulcer and to obtain biopsies for histologic analysis and assessment of Helicobacter pylori status. The mean basal acid output decreased from 7.3 to 1.9 mEq/hr during the 30-year period of follow-up (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The difference in eradication success with age has not been adequately explained, and studies observing this effect (including our own and those of Treiber) have not been specifically designed to elucidate a cause for this observation. While a clear relationship between age and gastric acidity has been demonstrated in many papers, 1 , 2 it has been shown that this relationship disappears when H. pylori status, corpus gastritis and smoking are controlled 2 . It is certainly possible that age may merely be a surrogate marker for corpus gastritis, but we agree with Treiber that the effect could equally be caused by pharmacokinetics or possibly differences in compliance.…”
supporting
confidence: 70%
“…The difference in eradication success with age has not been adequately explained, and studies observing this effect (including our own and those of Treiber) have not been specifically designed to elucidate a cause for this observation. While a clear relationship between age and gastric acidity has been demonstrated in many papers, 1 , 2 it has been shown that this relationship disappears when H. pylori status, corpus gastritis and smoking are controlled 2 . It is certainly possible that age may merely be a surrogate marker for corpus gastritis, but we agree with Treiber that the effect could equally be caused by pharmacokinetics or possibly differences in compliance.…”
supporting
confidence: 70%
“…Furthermore, other studies have shown that acid secretion increased with age 17,18. Consequently, it was thought that the decline of gastric acid was not the simple effect of physiological aging, but the result of gastric mucosal atrophy or H. pylori infection 7,19,2021,22.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric acid secretion decreases with age in H. pylori-positive subjects because of the increasing prevalence of Fundic Atrophic Gastritis with age [28]. Acid output decreases with advancing age [29]. In contrast to what is commonly stated, nearly 90% of elderly people in a study were able to acidify gastric contents, even in the basal, unstimulated state.…”
Section: Introductionmentioning
confidence: 69%